Revealing Regional Economic Potential Efforts to Increase the Development of Sharia-Based Leading MSMEs in Majene Regency - Irawati, Irawati; Rivai, Dian Rahmayanti; Fitriani, Nur (Universitas Alma Ata, 2024)
MSMEs contribute significantly to economic growth through their minimal investment capital requirements and comparatively high employment absorption rate, so MSMEs can be adjust and adapt flexibly to constantly changing market conditions. Increasing the number of MSMEs is not equal to an improvement the quality of MSMEs, largely to the classic problem of low productivity. This research aims to describe the phenomenon of superior SMEs and superior products, types of superior SMEs with exceptional products, and formulate policy strategies, following the potential of SMEs in Majene, West Sulawesi. This research used the documentation method with secondary data from books at BPS and Bapeda Majene Regency for the 2019-2023 period. The approach method and assessment process to find various types of SMEs and superior potential in the area will use the SWOT and Location Quotient analysis methods. The research results show that: Potential sectors that can drive the manufacturing sector, in terms of small-scale industries, are the agricultural, forestry, and fisheries industries, and the electricity and gas procurement sectors. Real Estate is the basic sector and the largest contributor to economic growth in Majene Regency. Policy strategies that can be implemented based on the SWOT, improving facilities and infrastructure, increasing workforce skills for small industries to maintain and improve the quality of their products. It is recommended that local governments continue to support small industries so that they remain a leading sector by making it easy for small industries to obtain the necessary permits, access capital, and marketing, and improve the skills of their workforce.